Agrobiological particularities of the new variety of soft winter wheat Nyva Kyivschyny - В. С. Хахула; Л. І. Уліч; М. І. Загинайло; З. С. Шпак; Н. В. Курочка (Plant Varieties Studying and Protection)
Results of studying morphoagrobiological characteristics and properties of a new variety ofsoftwinterwheat Nyva Kyivschyny are presented. It is determined that it has high genetic productivity potential, belongs to intensive variety type of universal use, is characterized by high winter and drought hardiness. This variety realizes its natural potential in a greater degree in case of growing after the best forecrop, at high soil fertility, with intensive agrotechnologies implementation and sowing at the end of the optimal time for appropriate agroclimatic zones.